A Computer Simulation Model of Optimum Sized Tractor Selection for Agricultural Mechanization - Adagunodo, Emmanuel Rotimi (Obafemi Awolowo University, 2014)
A computer simulation model for the selection of optimum-sized tractors based upon the durability and minimum cost analysis of the tractor has been developed. There is the need to optimize tractor sizes so as to minimize the cost and increase the productivity of farm mechanization process.